2022-RA-1348-ESGO Role of computed tomography (CT) scan based reporting system 'PAUSE' to predict surgical resectability in epithelial ovarian cancer. (20th October 2022) - Singhal, Seema; Sharma, Atul; Dhamija, Ekta; Kumar, Sunesh; Meena, Jyoti; Kumari, Rajesh; Singh, Anju; Kumari, Sarita; Natarajan, Jayashree; Sabarinath, Anu; Mandal, Amit; Chandra, Rudrika; et al.
Abstract : Introduction/Background: A novel 'PAUSE' reporting system was devised for standardization of reporting of CT based PCI in peritoneal malignancies and, also to emphasize increased focus on areas which often make the difference between optimal and suboptimal cytoreduction. The aims of current study were to evaluate the efficacy of CT scan-based protocol i.e. 'PAUSE', in predicting the optimal and suboptimal cytoreduction in EOC, and also to assess the role of intraoperative use of telescope to improve surgical PCI. Methodology: A prospective observational pilot study recruited 30 women with EOC undergoing primary debulking surgery. The CECT was evaluated in accordance with the 'PAUSE' protocol to assess resectability. Surgical PCI was calculated before surgery and was revised using intraoperative telescope. Agreement was done using kappa statistics and Bland-Altman agreement analysis. Results: The agreement between CT-PCI and surgical PCI was of low degree. Higher CT-PCI scores correlated with suboptimal resection; disease in regions 1, 3, 9, 10, 11 and 12 was more predictive of surgical outcome. The overall sensitivity, specificity, PPV and NPV of PAUSE with regards to prediction of surgical resectability was 81.3%, 35.7%, 59.1% and 62.5%, respectively. Diagnostic accuracy of PAUSE was 60%. Amongst the components, the maximum accuracy to predict sub optimal CRS was of U1 lesions, small bowel and mesentery involvement (66.7%), followed by U2 and A (53.3% and 50% respectively). New lesions were identified in 6 (20%) patients in subdiaphragmatic areas and the lesser sac using intra operative telescope in open surgery. Conclusion: 'PAUSE' did not show statistical significance with surgical outcome with modest diagnostic accuracy. Most useful parameters for prediction of surgical resectability, were the presence of U1/U2 lesions and the involvement of small intestine and mesentery; Presence of ascites (A component) was least predictive; thus, should not be used as a sole criterion.